2019
DOI: 10.1088/1748-9326/ab2f4c
|View full text |Cite
|
Sign up to set email alerts
|

Which are the factors influencing the integration of mitigation and adaptation in climate change plans in Latin American cities?

Abstract: As cities are major contributors to GHG emissions and places where people face multiple climate change impacts, their critical role in responding to climate change is becoming increasingly evident. Cities are developing climate change action plans (CCAPs) focusing their efforts on reducing GHG emissions and adapting to climate change impacts. Despite having the highest urban population in the world, there are a few studies on urban CCAPs in Latin America and the Caribbean (LAC) region. This study assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This could be because small cities have fewer resources and are less likely to be engaged in national and international networks ( Lioubimtseva and da Cunha, 2020 ). On the other hand, other studies suggested that there is not a statistical relationship between population size and the adaptive capacity of large cities ( Filho et al, 2019 ; Kim and Grafakos, 2019 ). These results contrast with our analysis, but it should be noted that neither the dependent variable nor the characteristics of the cities are comparable with our study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This could be because small cities have fewer resources and are less likely to be engaged in national and international networks ( Lioubimtseva and da Cunha, 2020 ). On the other hand, other studies suggested that there is not a statistical relationship between population size and the adaptive capacity of large cities ( Filho et al, 2019 ; Kim and Grafakos, 2019 ). These results contrast with our analysis, but it should be noted that neither the dependent variable nor the characteristics of the cities are comparable with our study.…”
Section: Discussionmentioning
confidence: 92%
“… Araos et al (2016) evaluated the degree of development of adaptation measures, whereas Reckien et al (2018) explored the spatial dimension of the adaptation plans. In this line, Kim and Grafakos (2019) also analysed the level of integration of adaptation and mitigation policies in 44 Latin American cities. Other studies have analysed the adaptation strategies by focusing on the indicators and metrics ( Arnott et al, 2016 ), the resilience and adaptive capacity of the cities ( Filho et al, 2019 ; Woodruff et al, 2018 ), or by comparing resilience plans with the local adaptation plans.…”
Section: Introductionmentioning
confidence: 99%
“…The Kullback-Leibler divergence measures the expected information for discriminating between discrete probability distributions P and Q when only observing P (Kullback and Leibler, 1951):…”
Section: Appendix A: Jensen-shannon Distance Derivationmentioning
confidence: 99%
“…LAC is among the most urbanized regions in the world where population densities in water-rich regions can be many times higher than arid regions, such as in Argentina. These high-density areas face particular vulnerability to water quality and supply reliability (Kim and Grafakos, 2019). For example, São Paulo faced severe water shortages during a 2014 drought, while Mexico City has steadily and rapidly depleted its groundwater supply (Aguilar-Barajas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is the second most urbanised region in the globe with 81% of population living in cities (United Nations 2018). Sustainability governance in Latin American cities is highly sensitive to the influence of international peers and donor priorities (Kim and Grafakos 2019). However, evidence is mounting that the replication of Northern cities' models in Latin America without adequate adaptation is prone to failure (e.g., Marchetti et al (2019)).…”
Section: Introductionmentioning
confidence: 99%